Pesan Moral Dalam Iklan Pahlawan Untuk Kakek: Analisis Semiotika Roland Barthes - Sarifah; Arfan; Afriansyah (Journal of Religion and Film, 2022)
Along with the times, information and communication technology has developed rapidly. Advances in technology have presented and provided a lot of information needed by society, especially for teenagers today through various mass media. The media used are usually print media and electronic media. The media has played a role in shaping the culture and lifestyle that will affect the morals of teenagers. This is what prompted the author to research the Hero ad for Grandpa which was produced by the Ramayana Department Store. This study aims to determine the meaning of denotations, connotations and myths contained in the Hero ad for Grandpa and to find out what moral messages are contained in it. The method used by the author in this study is a descriptive qualitative method with data collection techniques through observation and documentation. The analysis used is semiotic analysis with Roland Barthes analysis model. Through this semiotic analysis technique, the writer will know what messages are contained by dividing them into denotation, connotation and myth. This study was able to find signs and markers of the meaning of connotation, denotation and myth in the form of moral messages contained in the advertising film version of the Hero for Grandfather. The author found several moral messages in the advertisement, namely caring for the younger ones, maintaining health, patient nature, caring nature for the older ones, not complaining, empathy, self-sacrifice, sense of responsibility, respect for elders and love for those who are older. younger and love the homeland.